2017
DOI: 10.1115/1.4037026
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental and Model Study on Variable Mass Flow for Horizontal Wells With Perforated Completion

Abstract: The variable mass flow in perforated horizontal wells is very complex. One reason is that the perforation can increase the roughness of the pipe wall which will increase the frictional pressure drop. The other is the fluid boundary layer and velocity profile of axial flow will be changed due to the “mixing” of the inflow with the axial flow. The influences of the perforation parameters and flux rate on the pressure drawdown in horizontal wellbore are investigated. The perforation parameters include perforation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The result showed that the total pressure drop increases according to a larger acceleration pressure drop due to a higher flow rate through perforations and the total pressure drop increased with an increase in the number of perforations and vice versa. In this connection, a study by Jianguang et al [9] conducted an experimental study to calculate the effect of different perforation parameters, such as perforation diameter, and density, and to study the effect of the injection rate on the pressure drop in the horizontal well. The pipe tested in the experiment has an external diameter of 139.7 mm, an internal diameter of 124, a perforation diameter is 10-30 mm, and perforation angle is 180°, 90°, and 45°, and a perforation density of 8-24 SPM density.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the total pressure drop increases according to a larger acceleration pressure drop due to a higher flow rate through perforations and the total pressure drop increased with an increase in the number of perforations and vice versa. In this connection, a study by Jianguang et al [9] conducted an experimental study to calculate the effect of different perforation parameters, such as perforation diameter, and density, and to study the effect of the injection rate on the pressure drop in the horizontal well. The pipe tested in the experiment has an external diameter of 139.7 mm, an internal diameter of 124, a perforation diameter is 10-30 mm, and perforation angle is 180°, 90°, and 45°, and a perforation density of 8-24 SPM density.…”
Section: Introductionmentioning
confidence: 99%